2013
DOI: 10.1111/jbi.12168
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography of the supralittoral isopodLigia occidentalisaround the Point Conception marine biogeographical boundary

Abstract: Aim The Point Conception (PC) biogeographical boundary is defined by a transition between cold northern and warm southern water masses, accompanied by shifts in numerous ecological and environmental parameters. While these factors can potentially contribute to the genetic differentiation of lineages whose distributions span this boundary, few organisms exhibit genetic signatures of restricted gene flow across this region. We examine the effects of the PC boundary and other potential dispersal barriers on phylo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
61
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 41 publications
(72 citation statements)
references
References 51 publications
10
61
1
Order By: Relevance
“…Lastly, individuals from Cousine Island exhibit COI K2P divergences of 4.5–5.3% when compared to other localities (Mahé and Silhouette) within the inner islands. Interestingly, this pattern is similar to those previously reported for Seychellois herpetofauna from the inner islands (Rocha, Harris & Posada, 2011; Rocha, Posada & Harris, 2013; Silva et al, 2010) and to reports of cryptic diversity for other Ligia species, including L. occidentalis (Eberl et al, 2013; Hurtado, Mateos & Santamaria, 2010), L. hawaiensis (Santamaria et al, 2013; Taiti et al, 2003), L. baudiniana (Santamaria, Mateos & Hurtado, 2014), L. exotica and L. cinerascens (Yin et al, 2013), and L. oceanica (Raupach et al, 2014). The sum of our findings thus suggest the presence of 2–3 putative cryptic species of Ligia in the Seychelles: Aldabra Ligia being one, and those of Cousine and Silhouette + Mahé representing one or two putative species.…”
Section: Discussionsupporting
confidence: 89%
“…Lastly, individuals from Cousine Island exhibit COI K2P divergences of 4.5–5.3% when compared to other localities (Mahé and Silhouette) within the inner islands. Interestingly, this pattern is similar to those previously reported for Seychellois herpetofauna from the inner islands (Rocha, Harris & Posada, 2011; Rocha, Posada & Harris, 2013; Silva et al, 2010) and to reports of cryptic diversity for other Ligia species, including L. occidentalis (Eberl et al, 2013; Hurtado, Mateos & Santamaria, 2010), L. hawaiensis (Santamaria et al, 2013; Taiti et al, 2003), L. baudiniana (Santamaria, Mateos & Hurtado, 2014), L. exotica and L. cinerascens (Yin et al, 2013), and L. oceanica (Raupach et al, 2014). The sum of our findings thus suggest the presence of 2–3 putative cryptic species of Ligia in the Seychelles: Aldabra Ligia being one, and those of Cousine and Silhouette + Mahé representing one or two putative species.…”
Section: Discussionsupporting
confidence: 89%
“…Second, the broad distribution of this isopod spans multiple biogeographic regions (e.g., provinces and ecoregions), whose boundaries may constitute barriers for dispersal, as has been observed in other coastal isopods (e.g., Eberl et al. ). Our sampling in Brazil encompasses the boundary between the tropical southwestern Atlantic and the warm temperate southwestern Atlantic marine provinces (Spalding et al.…”
Section: Introductionmentioning
confidence: 81%
“…Evidence indicated that increasing seasonality and steepening of the sea surface temperature (SST) gradient that were most significant between 2.4 and 2.2 mya occurred in the ancient ECS, were located in the subtropics, whereas the ancient SCS located in the tropics showed minor or no cooling. Nonetheless, study of an isopod in North America and of a marine clam in Australia revealed that SST gradients can also be primary drivers of cladogenesis (Eberl, Mateos, Grosberg, Santamaria, & Hurtado, ; Li, Foighil, & Park, ). The SST gradient between the ECS and the SCS possibly also exerted an effect on the divergence of the clades studied here.…”
Section: Discussionmentioning
confidence: 99%